TUMPENG DALAM KEHIDUPAN ERA GLOBALISASI TUMPENG IN THE ERA OF GLOBALIZATION - Antonius Rizki Krisnadi (Program Studi Hospitality dan Pariwisata, 2020)
Tumpeng is a traditional culinary and be shown to represent the culinary of Indonesia’s archipelago. Tumpeng is always served at events such as: celebrating birthdays, thanksgiving, which are non-formal or formal. Globalization in the culinary field with the inclusion of traditional culinary from Asian, Middle Eastern and Western countries. The foreign culinary fame has succeeded in shifting the position of tumpeng as traditional culinary and Indonesian identity. Young socialites and today's family life are very fond of a variety of foreign traditional cuisines that are considered modern and prestige. A fast food traditional foreign culinary restaurant, turned into a place to celebrate the birthdays of sons and daughters, meetings, and thanksgiving. This will change the perception, mindset, and behavior of the younger generation towards Tumpeng, consider the culinary out of date and less fancy. Gradually, but surely the young generation of Indonesia who will come will not know tumpeng anymore, at the same time the loss of local meaning and wisdom contained in tumpeng. The problem is how to generate fame and sacredness of tumpeng in the past, to the community, especially the younger generation, and instill a sense of pride and love for tumpeng as a Indonesian traditional culinary. This study uses a qualitative-descriptive method. As for this research, tumpeng has experienced a very long historical development, various types of cone are in accordance with the intent and purpose of stakeholders. We must maintain and develop the philosophy contained therein and local wisdom in every type of cone in the current era of globalization.